ตอบ:
# (2 x ^ (8) z) / y ^ (4) #
คำอธิบาย:
# (x ^ ^ 3yz -2times2 (x ^ ^ 3y -2z) ^ 2) / (xyz ^ -1) #
ใช้กฎ: # (a ^ m) n = a ^ (mn) #
# => x ^ ^ 3yz -2times2 (x ^ (3 times2) Y ^ (- 2times2) Z ^ 2) / (xyz ^ -1) #
# => (2 x ^ 3yz ^ -2 ครั้ง (x ^ 6y ^ -4z ^ 2)) / (xyz ^ -1) #
# => (2 x ^ 3yz ^ -2timesx ^ 6y ^ -4z ^ 2) / (xyz ^ -1) #
ใช้กฎ: # a ^ m times a ^ n = a ^ (m + n) #
# => (2 x ^ (3 + 6) y ^ (1-4) z ^ (- 2 + 2)) / (xyz ^ -1) #
# => (2 x ^ (9) y ^ (- 3) z ^ (0)) / (xyz ^ -1) #
ใช้กฎ: # a ^ m / a ^ n = a ^ (m-n) #
# => (2 x ^ (9-1) y ^ (- 3-1) z ^ (0 + 1)) #
# => (2 x ^ (8) y ^ (- 4) z ^ (1)) #
ใช้กฎ: # a ^ -m = 1 / a ^ m #
# => (2 x ^ (8) z ^ (1)) / y ^ (4) #